Chemical composition of forage sorghum silage as a function of cutting frequency (Research, Society and Development, 2021)
The objective of this study was to evaluate the chemical characteristics of forage sorlum silage at different cutting frequencies. The research was conducted in the experimental sector at the Faculty of Technology of São Paulo in the premises of FATEC of Presidente Prudente-SP. The variety of forage sorb (Hybrid Silageiro Podium safra 2019 Biomatrix) was used. The experimental design used was in randomized blocks, with three subdivided plots, with four replications. The treatments were: T1 - APIC - before the ideal cut-off point; T2 - PIC - ideal cut-off point; T3 - DPIC - after the ideal cut-off point. It was verified that for the production of green biomass in the cut obtained a significant average of 39,761.9 tons of green mass per hectare, while in the regrowth it was 53,571.42. After the cuts of the rebrotas (second cut), comparing the production of green biomass in the three blocks, it was observed that they were higher in relation to the first cut. However, block 2 (PIC) of the regrowth obtained higher production with 60,714.28t when compared to blocks 1 and 3 with production of 54,285.71t and 45,714.28t. It was concluded that the increase in the cutting age reduced the crude protein content in relation to the raw mass, and caused an increase in the dry matter content of both in natura forage and silage.